Characterization of the Temporomandibular Joint of Southern Sea Otters (Enhydra lutris nereis) - Lieske, Danielle; Vapniarsky, Natalia; Verstraete, Frank J. M.; Leale, Dustin M.; Young, Colleen; Arzi, Boaz (Frontiers in Veterinary Science, 2015)
The structure–function relationship of the temporomandibular joint (TMJ) of southern sea otter has largely not been described. This study aims to describe the histological, biochemical, and biomechanical features of the TMJ disk in the southern sea otter. The TMJ disks from fresh cadaver heads of southern sea otter adult males (n = 8) and females (n = 8) acquired from strandings were examined. Following macroscopical evaluation, the TMJs were investigated for their histological, mechanical, and biochemical properties. We found that the sea otter TMJ disks are, in general, similar to other carnivores. Macroscopically, the TMJ disk was highly congruent, and the mandibular head was encased tightly by the mandibular fossa with a thin disk separating the joint into two compartments. Histologically, the articular surfaces were lined with dense fibrous connective tissue that gradually transitioned into one to two cell thick layer of hyaline-like cartilage. The disk fibers were aligned primarily in the rostrocaudal direction and had occasional lacuna with chondrocyte-like cells. The disk was composed primarily of collagen type 1. Biochemical analysis indicates sulfated glycosaminoglycan content lower than other mammals, but significantly higher in male sea otters than female sea otters. Finally, mechanical analysis demonstrated a disk that was not only stronger and stiffer in the rostrocaudal direction than the mediolateral direction but also significantly stronger and stiffer in females than males. We conclude that the congruent design of the TMJ, thin disk, biochemical content, and mechanical properties all reflect a structure–function relationship within the TMJ disk that is likely designed for the sea otter’s hard diet and continuous food intake.